Satisfaction with Access to Health Services: The Perspective of Estonian Patients with Rheumatoid Arthritis. (19th April 2012) - Põlluste, Kaja; Kallikorm, Riina; Meiesaar, Kersti; Lember, Margus
Abstract : In this cross-sectional study we explained the possible determinants of satisfaction with access to health services in patients with rheumatoid arthritis (RA). Of the 2000 randomly selected Estonian adult patients with RA, a total 1259 completed the survey. Regression analysis was used to analyse the predictors of patients' satisfaction with access to health services. Half of the respondents were satisfied with their access to health services. Factors that had a negative impact on satisfaction included pain intensity, longer waiting times to see the doctors, as well as low satisfaction with the doctors. Transportation costs to visit a rheumatologist and higher rehabilitation expenses also affected the degree of satisfaction. Patients who could choose the date and time at which they could visit the rheumatologist or who could visit their "own" doctor were more likely to be satisfied than patients whose appointment times were appointed by a healthcare provider.